Beauty and Essence of Mathematics: Students' Vision - Anupama Gupta (International Journal of Mathematics And its Applications, 2016)
Mathematics as a subject is indispensable in the development of any nation with respect to science and technology since mathematics itself is the language of science. The importance of Mathematics has never been greater than now and for the foreseeable future. Mathematical skills are crucial for a wide array of analytical, technological, scientific, economic and soft skill applications. Training students to become adept users of mathematics and to appreciate its usefulness is of paramount importance for the future. With mathematical resilience, students are motivated, confident, and persevere through negative situations. We seek to measure and track attitudes to mathematics, improve positivity and confidence, and ultimately, transform numeracy for all. It is, however, need of the hour for students' to develop interests and do well in mathematics, being the basic for all subjects and a tool for their future career. Teachers are the single most important resource for developing studentsтАЩ mathematical identities. By catering to the differing needs of students that derive from home environments, languages, capabilities, and perspectives, teachers allow them to develop a positive attitude to mathematics. A positive attitude raises comfort levels and gives students greater confidence in their capacity to learn and to make sense of mathematics. In recognition of the important role that mathematics plays, at all levels of the education system, the challenges in mathematics teaching is to attract young and adventures students into the field of a mathematics when at this time they may involve/fascinated by technology. Our main focus is to motivate the students, so that they must have fun and enjoyment while doing mathematical problems and the best chance at becoming excited about learning mathematics and they can enjoy the beauty & essence of mathematics.